Diálogos curriculares com a educação básica: a experiência do grupo de currículo do ensino fundamental no município de Feira de Santana (2010-2016) - Maia, Katty Lirane Haywanon Santos (2023)
The object of this research was to analyze the path of the Elementary School Curriculum Group (GCEF) in the Municipal Public Education Network of Feira de Santana, Bahia. The GCEF was a collective formed by teachers and technicians working in the network, based on a project proposed by the Municipal Department of Education - SEDUC, to draw up a curriculum proposal, with the participation of the school community and institutions linked to SEDUC, from 2010 to 2016, when the GCEF proposed holding Curriculum Dialogues as an action strategy. The general aim of this study was to analyze the potential for dialogue and confrontation by the GCEF in the process of building a Municipal Curriculum Proposal for Primary Education in Feira de Santana from the perspective of its members. This study used a qualitative approach based on Critical Social Theory, using educational policy, curriculum policy and participation as categories of analysis. To support this case study, the methodology used made it possible to map the field of study and research, analyze documents, questionnaires and interviews. The study concluded that, by analyzing educational policies for basic education, the possibility of constructing a curriculum policy with teacher participation became evident.